ANALISIS PENGARUH KUALITAS PRODUK DAN INOVASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE - Dharmawan, Darian; Berlianto, Margaretha Pink (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan, 2018)
Competition in the telecommunications industry is increased due to the rapid innovation of products and the increased product quality offered by the smartphone industry. But is it true that what is provided so far by the manufacturer is match with the needs of users? Therefore, this study aims to investigate the effect of product quality and product innovation in smartphone purchasing decisions. There are 3 hypotheses in this study. Product innovation consists of 5 dimensions, product quality consists of 8 dimensions and purchase decision consists of 5 dimensions. The sample in this study is 220 respondents of iPhone 7 users in Jabodetabek. Data analysis used in this research is multiple regression analysis. The results of this study showed that product quality has a positive effect on purchasing decisions,  product innovation has a positive effect on purchasing decisions and product quality and product innovation simultaneously have a positive effect on product quality.